Migration and remittances in Macedonia: A review - Barabara Dietz (Osteuropa-Institut Regensburg, 2010)
This paper explores migration movements and remittances patterns in Macedonia since independence and studies the migration policy challenges Macedonia will be likely to face after its entry into the EU. Concerning recent migration movements, considerable outflows from Macedonia are found as well as indications for a serious brain drain. Remittances to Macedonia - which are quite big - seem to constitute a relevant support for a number of households and can be expected to diminish the incidence of poverty. In the light of the EU accession process, the Macedonian government will have to introduce policies which enhance the opportunities of migration and remittances and reduce their risks.
Keywords: F22; F24; 330; Macedonia; migration; remittances; Internationale Wanderung; Brain Drain; Rücküberweisung (Migranten); EU-Erweiterung; Mazedonien